.,TSRS techninių bibliotekų istorijos" kurso parengimas Maskvos kultūros institute - Karatygina, Tatyana (Knygotyra, 1986)
One of the characteristic features in the history of the libraries of the last century has been the rapid development of the special libraries and among them of the technical libraries in the first place.This development was caused by the cardinal social-economic and technological changes in the world and particularly in the USSR. This fact has urged the Ministry of Culture of USSR to take iniciative in introducing in the Institutes of Culture and other higher educational establishments with faculties of library science of a special course of the history of technical libraries. The programme of this course was created in the Moscow State Institute of Culture. In this paper the structure of this course is outlined and the experience of teaching analysed.